Pengaruh Kualitas Pelayanan Food And Beverage Service Terhadap Kepuasan Pelanggan di Swiss-Bellhotel Ambon - Merlin Imelda Solemede; Gilbert Alvin Rumalatu; Fransiska J Pattiruhu (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to determine the influence of food and beverage service quality on customer satisfaction at Swiss-Bellhotel Ambon. There were 120 samples but 80 samples were used for processing. Data collection used a questionnaire with a Likert scale. The analytical method used in this research is a simple linear regression analysis method with the SPSS 26 application. The research results based on (t test) show that service quality has a significant effect on customer satisfaction with a significant value of 0.000<0.05 and obtained an Rsquare of 0.174% influenced by variables. independent of service quality, while 82.6% is influenced by other variables not examined in this research.